Aortic hemodynamic and morphological analysis before and after repair of thoracoabdominal aortic aneurysm using a G-Branch endograft - Wang, Jiabin; Fan, Tingting; Zhang, Hongpeng; Ge, Yangyang; Lu, Weihang; Liu, Feng; Rong, Dan; Guo, Wei (Frontiers in Physiology, 2023)
Background and Objective: The G-Branch endograft is a novel multibranched “off-the-shelf” device used to repair thoracoabdominal aortic aneurysms (TAAAs). This report describes the hemodynamic and morphological performance of the G-Branch endograft in a human patient with TAAA. Materials and methods: We retrospectively reviewed the computed tomography angiography scans and clinical data of a woman in whom TAAA was treated using a G-Branch endograft. Patient-specific three-dimensional models were reconstructed, and computational fluid dynamics and morphological and hemodynamic indicators were analyzed before and after implantation of the device. Results: From a morphological perspective, there was an increase in cross-sectional area in the G-Branch endograft and all bridging stent grafts over time. Blood flow was redistributed among the renovisceral arteries, with a decrease in flow rate in the celiac artery and an increase in the left renal artery. Laminar blood flow was smoother and more rapid after implantation of the G-Branch device and remained stable during follow-up. In the bridging stent grafts, flow recirculation zones were found in the bridging zones of the celiac and superior mesenteric arteries as well as the distal sealing zones of both renal arteries. Furthermore, higher time-averaged wall shear stress and a lower oscillatory index and relative resident time were found in the G-Branch endograft and bridging stent grafts. Quantitative analysis showed obvious reduction in the surface area ratio of the elevated time-averaged wall shear stress area and surface area ratio of the relative resident time after G-branch implantation. Conclusions: The revascularization of branch vessels occurred following G-branch implantation, with improvements arising not only from morphological changes but also from hemodynamic alterations. The long-term performance of the G-Branch endograft needs further investigation and clinical validation.